Mechanism of rainfall triggering landslides in Kulonprogo, Indonesia - Agus Setyo Muntohar, Jazaul Ikhsan,Eko Soebowo (American Society of Civil Engineers., 2013)
A landslide occurred during intense rainfall on 17 to 22 November 2012 in Kulonprogo, Indonesia is evaluated in this paper. The main objective of this work is to investigate the mechanism of rainfall induces landslide and thereby determine the critical time of instability. A finite element seepage analysis was performed to simulate the changes in pore water pressure during the rainfall event. Incorporation seepage model, the limit equilibrium slope stability method was applied to calculate the variations in the factor of safety during the event. Effective stress Mohr–Coulomb failure criterion was applied in the soil failure modeling. For the investigated site, the trend of the factor of safety indicates that the critical time for failure occurs about three days after the intense-rainfall commences. Seepage caused rising of the ground water table, and increased pore water pressure. The slope instability was controlled by the residual shear strength.